The Effect Of Playing Collage On The Development Of Fine Motorics In Preschool Children - Rehana, Rehana; Nurul Komariyah; Intan Wilujeng (CV. AFDIFAL MAJU BERKAH, 2024)
The low development of children's fine motor skills preschool. This can be seen when children do collage play activities, many children are not neat in making collage patterns.To determine the effect of playing collage on the fine motor development of preschool children in the kindergarten Keiynan Dan Mawadah Warohmah Palembang City In 2021.This type of research is pre-experimental design with one group pretest posttest. The study population was all children in KB keiynan dan KB Mawadah Warohmah Kota Palembang. The sampling technique is Simple Random Sampling. The number of samples is 26 respondents who have met the inclusion and exclusion criteria. Data analysis techniques using the Wilcoxon. Based on the results of bivariate test results using the Wilcoxon, a significant value is obtained (ρ-value = 0,000), so <0.05.There is an effect of playing collage on the fine motor development of preschool children in the kindergarten Keiynan Dan Mawadah Warohmah Palembang City In 2021.The results of this study can be used as consideration and reference for those who want to further develop research in the same field, especially in improving the fine motor skills of preschool children.